Building Community Capacity From Evidence to Action (2015-2016) : Profile of English-speaking Seniors : Rocher-Percé - Pocock, Joanne (Seniors Action Quebec (SAQ), 2015)
The Seniors Action Québec (SAQ) project is designed to mobilize English-speaking (ES) seniors (65+) and their communities in four regions of the province (Gaspésie, Greater Quebec City, Outaouais and the North Shore). This will be done by creating a network among English language regional community organizations to amplify the voice of minority language seniors and enhance their contribution to the vitality of their communities. The project will ready the network to identify critical issues affecting English-speaking seniors, establish regional action plans to address seniors’ priorities and to generally promote awareness of provincial and regional organizations serving the interests of the 65 years and over age group.